(untitled) (REMUNOM, 2024)
The search for efficiency and effectiveness in the business environment makes companies develop strategies to maximize the use of available resources, especially human resources. In this sense, one of the oldest business activities, and still applied today, is the division of work into departments, or departmentalization. Given the above, the objective of this study is to present departmentalization as a management tool for organizations, highlighting its structuralist and hierarchical character, and adding to these initial bases new visions that have emerged over time. To this end, a study was carried out involving a small national company and, subsequently, a comparison with a large multinational company. It was found that small companies, due to the fact that they have a smaller number of human resources, have more difficulty in dividing work, almost always culminating in an accumulation of functions in departments.